Anesthesia Management on Neonatal Atresia Duodenum with Gastric Outlet Obstruction: Case Report - Hidayanti, Dwi; Woyka, Swanita (Jurnal Ners, 2024)
This case report presents a thorough investigation into the condition of a 1-day-old male neonate diagnosed with Atresia Duodenum, elucidating the complexities of clinical manifestation, diagnostic assessments, surgical intervention, and post-operative care. The neonate displayed a spectrum of symptoms, encompassing vomiting, neonatal pneumonia, and gastric outlet obstruction, coupled with a history of low birth weight, BBLR, and polidaktili. The management of neonates with Atresia Duodenum is underscored as challenging, emphasizing the indispensable role of a multidisciplinary approach for optimal outcomes. Born at 36 weeks gestation through caesarean section due to polyhydramnion, the neonate presented distinct clinical features alongside relevant laboratory irregularities. Radiographic confirmation of the diagnosis revealed stomach dilatation with minimal air in the distal intestine. The subsequent Atresia Duodenum bypass procedure on October 10, 2023, was executed with scrupulous attention to intraoperative vital signs and anesthesia management. Post-operatively, the neonate demonstrated spontaneous breathing and stable vital signs but exhibited weakness upon NICU transfer. This in-depth analysis underscores the intricate nature of Atresia Duodenum, accentuating the complexities inherent in its diagnosis, surgical intervention, and post-operative care. Radiographic modality played a pivotal role in confirming the diagnosis, while the surgical procedure underscored the significance of timely and precise intervention. The post-operative phase unveiled persistent challenges, emphasizing the systemic impact of Atresia Duodenum and necessitating vigilant multidisciplinary care. This case report contributes nuanced insights to medical literature, emphasizing the imperative of a collaborative and multidisciplinary approach involving neonatologists, surgeons, and anesthesiologists. Ongoing research and shared experiences will further refine comprehension and elevate care standards for neonates with Atresia Duodenum.